Polish Independent Press Review, no. 6 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Polish-Czechoslovak Solidarity: More Cooperation across the Border / by Anna PomianProminent activists from Polish-Czechoslovak Solidarity have published a statement on the occasion of Mikhail Gorbachev's visit to Poland. The declaration comes one year after a support group calling itself the Circle of Friends of Polish-Czechoslovak Solidarity was set up to coordinate activity across the two borders and to make the group better known. State Education: Parents Press Their Rights / by Anna PomianThe increasing frustration of teachers, parents, and schoolchildren with state education in Poland has led to the growth of interest in private education and in parental participation in state schools. Life on a State Farm / by Anna PomianA recent article in the Polish independent press discussed some of the problems encountered on state farms. A Paper for Vegetarians / by Anna PomianAs the Polish independent press has expanded in scope, it seems that few areas of life remain untouched; a paper specifically for vegetarians has recently appeared in Poland. Profiles of Major Independent Polish Publications: "Hutnik" / by Michał Kołodziej"Hutnik - Pismo członków NSZZ 'Solidarność' Huty im. Lenina" is a weekly publication appearing in Nowa Huta.